2020
DOI: 10.1016/j.heliyon.2020.e05590
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Non-Acid-Forming material layering for the prevention of acid mine drainage of pyrite and jarosite

Abstract: Encapsulation is a typical method used to prevent potential acid mine drainage (AMD) in overburden piles. In this method, Potentially Acid-Forming (PAF) material is covered with either Non-Acid-Forming (NAF) material or alkaline material to minimize water infiltration and/or oxygen diffusion through rock pores. The physical and chemical characteristics and thickness of the NAF material layer are critical factors affecting the successful prevention of AMD. Therefore, this study evaluated the method of NAF mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The materials are then compacted to prevent water infiltration and oxygen reaction with sulphidic minerals contained in OB-PAF materials [35,37]. Research in the Lati coal mine [43] as well as in the Sangatta and Bengalon coal mines [44] showed that encapsulation is the most effective method in preventing AMD. With the increasing use of coal as an energy source, the amount of coal combustion ash (CCA) produced has also increased.…”
Section: Land Clearingmentioning
confidence: 99%
“…The materials are then compacted to prevent water infiltration and oxygen reaction with sulphidic minerals contained in OB-PAF materials [35,37]. Research in the Lati coal mine [43] as well as in the Sangatta and Bengalon coal mines [44] showed that encapsulation is the most effective method in preventing AMD. With the increasing use of coal as an energy source, the amount of coal combustion ash (CCA) produced has also increased.…”
Section: Land Clearingmentioning
confidence: 99%
“…Some research reported that AMD contains dissolved metals such as iron, aluminium, zinc, copper, and other metals (Brar et al, 2022;Shi et al, 2022;Zhang et al, 2022). Therefore, AMD entering the environment can cause pollution to water bodies and soil, and also it can have adverse effects on living organisms (Abfertiawan et al, 2020) .…”
Section: Introductionmentioning
confidence: 99%
“…In general, the dry cover method is often used to prevent the formation of AMD (Lu et al, 2013) . The principle of this technique is an oxygen barrier where rocks having the potential to produce acidity will be covered with non-acidity materials (Abfertiawan et al, 2020) . Some materials that can be used as cover are organic soil (Demers et al, 2017) , fly ash (Win et al, 2020) , green liquor dregs (Mäkitalo et al, 2014) , and others.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of acid water drainage aggravates the water quality from coal mining pits [4], which is the result of a reaction among sulfide minerals, oxygen, and water [5] [6], especially from exposed PAF materials on the pit wall. Acid mine drainage formation may continue after mine closure as pit lakes develop.…”
Section: Introductionmentioning
confidence: 99%